2017
DOI: 10.1016/s0140-6736(17)32013-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of multidrug-resistant bacteria in the occupied Palestinian territory: a cross-sectional study

Abstract: Background Antimicrobial resistance is a worldwide threat to public health. WHO has created several resolutions and strategies on this subject at the World Health Assembly. In May, 2015, WHO published a global action plan to mitigate antimicrobial resistance, including tracking and global surveillance focusing on improving awareness and understanding of this issue. The aim of this study was to screen for carbapenem-resistant bacteria in the occupied Palestinian Territory, to investigate the mechanisms behind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This gene confers carbapenem resistance to bacteria. Several studies confirmed the emergence of carbapenem resistant strains of bacteria [32,34,36,39]. One study showed that carbapenem resistant bacteria were having cabapenemase OXA-51 gene group in all isolates and one isolate from Gaza was positive for NDM-2 [40].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This gene confers carbapenem resistance to bacteria. Several studies confirmed the emergence of carbapenem resistant strains of bacteria [32,34,36,39]. One study showed that carbapenem resistant bacteria were having cabapenemase OXA-51 gene group in all isolates and one isolate from Gaza was positive for NDM-2 [40].…”
Section: Discussionmentioning
confidence: 90%
“…The study of Rida et al [39] focused on carbapenem resistance among GNB isolated from clinical and environmental hospital samples. The study tested 210 clinical samples, 150 environmental swabs, and 110 air samples.…”
Section: Resistance Pattern For Pathogens Isolated From Burn Patients Units Hcw and Hospital Settingsmentioning
confidence: 99%
See 1 more Smart Citation